2020
DOI: 10.1007/s11896-020-09369-z
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the Prevalence and Situational Characteristics of Hostage and Crisis Negotiation in England: an Analysis of Pilot Data from the National Negotiator Deployment Database

Abstract: The following paper outlines the findings from an exploratory analysis of the hostage and crisis negotiator deployment database that was piloted within Norfolk and Suffolk Constabularies prior to national rollout of a centralised and standardised online recording mechanism for negotiator deployments across the majority of police forces within the UK. The research utilised a descriptive research design, whereby the secondary data from an initial 24-month recording period was analysed using descriptive statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The concept of English HCN deployment focusing on crisis intervention, as opposed to incidents with hostage or victim involvement, is also a key finding, which is supported by Alexander's () Scottish findings whereby only 6.0% of the incidents responded to over a 3‐year period involved hostages, and Grubb's () findings, whereby only 6.6% of deployments involved hostages or victims. These findings do, however, contrast heavily with Mohandie and Meloy's () American findings that suggest that 45.2% of the cases they reviewed were classified as “hostage incidents.” Although the current research findings cannot be directly compared to those of Alexander (), Grubb (), and Mohandie and Meloy () due to differences in methodology, they raise the question of whether the day‐to‐day role of HCNs differs internationally. Differences in firearms laws and policing styles adopted, for example, may influence the status quo in relation to the type of incident that HCNs get deployed to.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The concept of English HCN deployment focusing on crisis intervention, as opposed to incidents with hostage or victim involvement, is also a key finding, which is supported by Alexander's () Scottish findings whereby only 6.0% of the incidents responded to over a 3‐year period involved hostages, and Grubb's () findings, whereby only 6.6% of deployments involved hostages or victims. These findings do, however, contrast heavily with Mohandie and Meloy's () American findings that suggest that 45.2% of the cases they reviewed were classified as “hostage incidents.” Although the current research findings cannot be directly compared to those of Alexander (), Grubb (), and Mohandie and Meloy () due to differences in methodology, they raise the question of whether the day‐to‐day role of HCNs differs internationally. Differences in firearms laws and policing styles adopted, for example, may influence the status quo in relation to the type of incident that HCNs get deployed to.…”
Section: Discussionmentioning
confidence: 82%
“…Murphy (), for example, reported on HOBAS data from 2001 and revealed that 68.4% ( n = 1251) of incidents involved some form of firearm and figures reported by Hammer () suggest that firearms are present in 56.0% of cases. Comparative figures taken from Scotland (14.0%; Alexander, ) and two regional police forces in England (13.3%; Grubb, ) suggest that this figure is much lower within the U.K.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, although the model provides a thorough depiction of the negotiation procedure, it has been developed mainly on the basis of negotiators' experiences of overt crisis and hostage negotiation (with emphasis on the former as this constitutes the majority of negotiator deployments in England; Grubb, 2017). As it stands, the model fails to identify any procedural or communicative differences that may exist when negotiating in a covert as opposed to overt format.…”
Section: Limitations Future Directions and Conclusionmentioning
confidence: 99%
“…Interviewees consisted of a sub-sample of participants who took part in an earlier quantitative phase of the research (see Grubb, Brown, & Hall, 2015, 2017.…”
Section: Participantsmentioning
confidence: 99%